T3 HORMONE AS AN EFFECTIVE THERAPY FOR HEART FAILURE WITH PRESERVED EJECTION FRACTION: Effects on Ca2+ transients and contractility - Gonçalves, Alexandre Manuel Monteiro (2018)
Dissertação de Mestrado em Investigação Biomédica apresentada à Faculdade de Medicina